The Effect of a Home Delivery Meal Service of Energy- and Protein-Rich Meals on Quality of Life in Malnourished Outpatients Suffering from Lung Cancer: A Randomized Controlled Trial. (3rd April 2017) - Leedo, Eva; Gade, Josephine; Granov, Sabrina; Mellemgaard, Anders; Klausen, Tobias Wirenfeldt; Rask, Katrine; Astrup, Arne
ABSTRACT: Undernutrition is prevalent in cancer patients and associated with increased incidence of complications and mortality. We investigated the effects of a home delivery meal service, providing a selection of energy-dense, protein-rich meals, on quality of life (QoL) in malnourished lung cancer patients. Forty lung cancer patients with nutritional risk score ≥3 (NRS-2002) were randomized to control or intervention. The intervention group was offered energy- and protein-rich main meals and snacks, delivered 3 times per week. The control group continued their habitual diet. Primary endpoint, QoL, and secondary endpoints were assessed at baseline, and after 6 and 12 wk. Data on unplanned readmissions, length of hospital stay, and mortality were collected 3 and 6 mo post-intervention. Intervention group improved standard Chair Stand Test (30-s CST) after 6 and 12 wk ( P < 0.01) compared to control. Intervention exerted a significant positive effect on performance score after 12 wk ( P = 0.047). Increased energy and protein intakes were strongly associated with improved QoL, functional score, hand grip strength, symptom and performance scores. Food delivery service with energy- and protein-rich main meals and snacks can improve lower body strength and performance status in malnourished lung cancer patients.